Combining text mining and data mining for bug report classification. Issue 3 (23rd February 2016) - Zhou, Yu; Tong, Yanxiang; Gu, Ruihang; Gall, Harald
Abstract: Bug reports represent an important information source for software construction. Misclassification of these reports inevitably introduces bias. Manual examinations can help reduce the noise, but bring a heavy burden for developers instead. In this paper, we propose a multi‐stage approach by combining both text mining and data mining techniques to automate the prediction process. The first stage leverages text mining techniques to analyze the summary parts of bug reports and classifies them into three levels of probability. The extracted features and some other structured features of bug reports are then fed into the machine learner in the second stage. Data grafting techniques are employed to bridge the two stages. Comparative experiments with previous studies on the same data—three large‐scale open‐source projects—consistently achieve a reasonable enhancement (from 77.4% to 81.7%, 76.1% to 81.6%, and 87.4% to 93.7%, respectively) over their best results in terms of overall performance. Additional comparative empirical experiments on other seven popular open‐source systems confirm the findings. Moreover, based on the data obtained, we also empirically studied the impact relation between the underlying classifiers and various other properties of the combined model. A prototypical recommender system has been developed to demonstrate the applicability of our approach. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The overview of combining text mining and data mining for bug report classification